Home Irrigation and Landscape Combinations for Water Conservation in Florida - Melissa B. Haley; Michael D. Dukes; Grady L. Miller; Dorota Z. Haman (EDIS, 2005)
Irrigation has become commonplace for residential homeowners desiring high quality landscapes in Florida. Turfgrass is a key landscape component and normally the most commonly used single type of plant in the residential landscape. Although Florida has a humid climate where the precipitation rate, on average, is greater than the evapotranspiration rate, the winter and spring are normally dry. The dry winter/spring weather and sporadic large rain events in the summer coupled with low water holding capacity of the soil make irrigation necessary for the high quality landscapes desired by homeowners. This document is ABE 355, one of a series of the Department of Agricultural and Biological Engineering, UF/IFAS Extension. Original publication date March 2005.